Promoting Worker Health : a New Approach to Employee Benefits in the Twenty-First Century - Hadler, Nortin M.; Carter, Stephen P. (The University of North Carolina Press, 2018)
"In this extended essay, Nortin M. Hadler and Stephen P. Carter introduce a new approach to reforming the American health-care system--a plan they call the Universal Workers' Compensation Model (UWCM). Drawing on Hadler's expertise as a physician and Carter's as an attorney, the two have conceived the UWCM as a state-level alternative that would supersede current solutions debated at the national level. They begin by summarizing the history and present complexity and irrationality of America's health-insurance system. They then lay out the key concepts underlying the UWCM regime and the practical policy steps necessary to enact it. At the heart of the UWCM is a broader understanding of what constitutes worker's health, one grounded in scientific research and cognizant of the wide range of physical and mental illnesses that can afflict workers. The UWCM stipulates a single policy providing rational and reasoned recourse for universal risks: illness, injury, disability, and death."--Cover